Periodontal disease and its complications in cats from a shelter in the Central Region of Rio Grande do Sul - Roberto M. Maciel; Renata D. Mazaro; João P.F. Silva; Douglas M. Lorenzetti; Alana Herbichi; Milena C. Paz; Cristiane C. Danesi; Rafael A. Fighera (Pesquisa Veterinária Brasileira, 2020)
ABSTRACT: Periodontal disease is the most common infectious disease that occurs in feline patients. Although it occurs in both sexes, different age groups, and any breeds, the prevalence and severity seem much higher in cats living in animal shelters. This paper aimed to describe the clinical, radiological, cytopathological, and virological aspects of periodontal disease and its complications in cats, based on these aspects and, consequently, on the importance it brings to cat feline medicine in shelter cats. For this, nine cats with periodontal disease from a single animal shelter were evaluated. These cats demonstrated a disease characterized by halitosis, excessive salivation, and oral discomfort. Lymphadenomegaly of the mandibular and retropharyngeal lymph nodes was observed in 44.4% of the cases. Oral lesions consisted of varying degrees of gingival hyperemia, complete loss of free gingival margins, and consequently gingival retraction, dental calculus deposition, dental mobility, complete exposure of the furcation of premolars and molars, and dental roots of canines and incisors, loss of bone radiopacity due to alveolar bone resorption and tooth loss. Complications included chronic ulcerative paradental stomatitis (22.2%), faucitis (22.2%), and chronic gingivostomatitis (11.1%). None of the cats affected by periodontal disease was positive for FIV or FeLV. In 33.3% of the cases, cats were carriers of feline calicivirus, but not feline herpesvirus.